Health system resilience in managing the COVID-19 pandemic: lessons from Singapore. Issue 9 (16th September 2020) - Chua, Alvin Qijia; Tan, Melisa Mei Jin; Verma, Monica; Han, Emeline Kai Lin; Hsu, Li Yang; Cook, Alex Richard; Teo, Yik Ying; Lee, Vernon J; Legido-Quigley, Helena
Abstract : Singapore, one of the first countries affected by COVID-19, adopted a national strategy for the pandemic which emphasised preparedness through a whole-of-nation approach. The pandemic was well contained initially until early April 2020, when there was a surge in cases, attributed to Singapore residents returning from hotspots overseas, and more significantly, rapid transmission locally within migrant worker dormitories. In this paper, we present the response of Singapore to the COVID-19 pandemic based on core dimensions of health system resilience during outbreaks. We also discussed on the surge in cases in April 2020, highlighting efforts to mitigate it. There was: (1) clear leadership and governance which adopted flexible plans appropriate to the situation; (2) timely, accurate and transparent communication from the government; (3) public health measures to reduce imported cases, and detect as well as isolate cases early; (4) maintenance of health service delivery; (5) access to crisis financing; and (6) legal foundation to complement policy measures. Areas for improvement include understanding reasons for poor uptake of government initiatives, such as the mobile application for contact tracing and adopting a more inclusive response that protects all individuals, including at-risk populations. The experience in Singapore and lessons learnt will contribute to pandemic preparedness and mitigation in the future.